The efficacy of antimalarial monotherapies, sulphadoxine-pyrimethamine and amodiaquine in East Africa: implications for sub-regional policy. - East African Network for Monitoring Antimalarial Treatment (EANMAT) (2003)
Between 1998 and 2001, Kenya, Uganda, Tanzania, Zanzibar, Rwanda and Burundi changed antimalarial drug policy, in the face of widespread chloroquine resistance. The new first-line treatment is either sulphadoxine-pyrimethamine (SP) monotherapy, or a combination of SP with either chloroquine or amodiaquine. Two national malaria control programmes, Burundi and Zanzibar, have decided upon amodiaquine-artesunate as their first-line treatment, although SP will continue to fill this role until the new policy can be implemented. Given the broad uniformity of parasite chemoresistance in the six countries, The East African Network for Monitoring Antimalarial Treatment (EANMAT) has focused attention on, and worked towards, a sub-regional antimalarial drug policy, where the evidence base would be the entire portfolio of network in vivo test results. Currently, there are several different antimalarial drug policies within the EANMAT area: the intention is to eventually replace this plethora of policies with a single, sub-regional policy based upon combination therapy. Currently, successful malaria treatment depends primarily upon the efficacy of SP, and of amodiaquine, which is either a component of first-line treatment, or the second line drug. This report addresses the results of WHO in vivo tests on these two monotherapies within the network. Results are analysed to assess the evidence for change in parasite susceptibility over time; the range of susceptibility to each drug within countries, and the implications of test results on policy.